Responsivitas Pemerintah Terhadap Perlindungan Anak (Anjal dan Gepeng ) di Kantor Dinas Sosial Kota Makassar - Nur Faisah; Jaelan Usman; Adnan Ma'ruf (Department of Public Administration, Muhammadiyah University of Makassar, 2015)
This research aims to examine how theresponsiveness of government to the protection of children, and the measures had taken by the government on issues of child protection in Makassar. The research was conducted at government institutions in Makassar, the Agency Social Officeof Makassar. The research method is descriptive qualitative, the source of data are from primary and secondary data. The Data were obtained by interview and observation in the field. The result indicates the responsiveness of the government of Makassar is responsive for child protection. However, it is not optimal. This can be seen from the ability to recognize the needs of children, priority of service, and the development of child protection programs is still limited, since the government still relies on other agencies that care for child protection issues.Keywords: responsiveness, child protection Penelitian ini bertujuan mengkaji bagaimana responsivitas pemerintah terhadap perlindungan anak, dan langkah-langkah yang ditempuh pemerintah dalam permasalahan perlindungan anak di Kota Makassar. Penelitian ini dilaksanakan pada institusi pemerintah di Kota Makassar, yaitu Kantor Dinas Sosial Kota Makassar. Jenis penelitian ini adalah deskriptif kualitatif, data bersumber dari data primer dan data sekunder. Data di peroleh dengan teknik wawancara dan observasi di lapangan. Hasil penelitian menunjukkan responsivitas pemerintah Kota Makassar terhadap perlindungan anak cukup responsif, namun demikian responsivitas tersebut belum optimal. Hal ini bisa dilihat dari kemampuan mengenali kebutuhan anak, prioritas pelayanan, dan pengembangan program perlindungan anak masih terbatas, karena pemerintah masih bertumpu pada lembaga-lembaga lain yang perduli pada permasalahan perlindungan anak. Kata kunci: responsivitas, perlindungan anak